Development, competition and Hillbrow: the Inner-City High Schools Drama Festival 2005-2015, a community arts project - Madiba, Zanele Suzen (My University, 2016)
This study looks into the artistic strategies employed by the Inner-City High Schools Drama Festival to promote an appreciation for arts and culture programmes in inner-city high schools and beyond, and, by extension, reflects on how the festival impacts on participants’ perceptions of Hillbrow as home. Through an analysis of South African art historian Lize van Robbroeck’s conceptual framework of community arts centres, this case study unpacks how site specificities of the centre being in Hillbrow, starts to debunk what has become a widely understood framework of arts centres as inherently pro-marginal, thereby associated with ‘blackness’, both during apartheid and post-apartheid. Qualitative methods such as semi-structured interviews with the Hillbrow Theatre Project staff, facilitators and school teachers, focus group discussions with school-goers, letters and organisational documents have therefore been used in order to get a deeper understanding of the workings of the Outreach Foundation as a centre and its artistic programme under the Hillbrow Theatre Project called the Inner-City High Schools Drama Festival. The study reveals that the artistic strategies employed by the Inner-City High Schools Drama Festival are effective in promoting an appreciation for an arts and culture programme, and it further shows that the festival can indeed effect some measure of change in participants’ attitudes about Hillbrow as home.
This thesis is submitted to the Faculty of Humanities, University of Witwatersrand, in fulfilment of the requirements for the degree of Master of Arts in Arts and Culture Management by dissertation, 2016
Keywords: Drama festivals; Amateur plays; Community arts projects; Participatory theater